The Differences in Junior High School Students’ Critical Thinking Skills in Tems of Learning Styles Using Construct 2 Game Media in Natural Science (IPA) Subject Biology - Handoko, Akbar; Hidayah, Nur; Sri Anggoro, Bambang; Ferry, Dharma (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2025)
The development of students’ critical thinking skills has become a central objective in contemporary science education, yet conventional instructional approaches often fail to actively engage learners in higher-order cognitive processes. This study aims to examine the effects of Construct 2 game-based learning media and learning styles on junior high school students’ critical thinking skills. A quantitative quasi-experimental design with a 2 × 3 factorial structure was employed, involving 67 seventh-grade students divided into an experimental group (Construct 2) and a control group (video-based learning). Data were collected using a validated critical thinking test and a learning style questionnaire, and analyzed using two-way ANOVA. The results revealed a significant main effect of learning media, with students in the game-based group achieving higher critical thinking scores than those in the video-based group. A significant effect of learning styles was also identified, indicating differences in critical thinking performance across visual, auditory, and kinesthetic learners. However, no significant interaction effect was found between learning media and learning styles. These findings suggest that interactive game-based learning provides a more effective approach to enhancing students’ critical thinking skills and can be applied consistently across diverse learner characteristics. The study contributes to the integration of educational technology and cognitive development by highlighting the role of interactive media in fostering higher-order thinking. Perbedaan Keterampilan Berpikir Kritis Siswa Sekolah Menengah Pertama Ditinjau dari Gaya Belajar Menggunakan Media Game Construct 2 pada Mata Pelajaran IPA Biologi ABSTRAK: Pengembangan keterampilan berpikir kritis siswa menjadi salah satu tujuan utama dalam pembelajaran sains modern, namun pendekatan pembelajaran konvensional sering kali belum mampu mendorong keterlibatan kognitif yang optimal. Penelitian ini bertujuan untuk menganalisis pengaruh media pembelajaran berbasis game Construct 2 dan gaya belajar terhadap keterampilan berpikir kritis siswa sekolah menengah pertama. Penelitian ini menggunakan pendekatan kuantitatif dengan desain quasi-eksperimen dan rancangan faktorial 2 × 3 yang melibatkan 67 siswa kelas VII yang dibagi ke dalam kelompok eksperimen (Construct 2) dan kelompok kontrol (media video). Data dikumpulkan melalui tes berpikir kritis yang telah divalidasi serta angket gaya belajar, kemudian dianalisis menggunakan two-way ANOVA. Hasil penelitian menunjukkan adanya pengaruh signifikan media pembelajaran, di mana siswa yang belajar menggunakan media berbasis game memperoleh skor berpikir kritis lebih tinggi dibandingkan dengan siswa yang menggunakan media video. Selain itu, terdapat pengaruh signifikan gaya belajar terhadap keterampilan berpikir kritis, yang menunjukkan adanya perbedaan kemampuan berdasarkan karakteristik visual, auditori, dan kinestetik. Namun demikian, tidak ditemukan interaksi yang signifikan antara media pembelajaran dan gaya belajar. Temuan ini menunjukkan bahwa pembelajaran berbasis game yang interaktif lebih efektif dalam meningkatkan keterampilan berpikir kritis dan dapat diterapkan secara konsisten pada berbagai karakteristik siswa